Translocação de nematicidas e inseticidas nas raízes do cafeeiro (Coffea arabica L.) e seus efeitos sobre Meloidogyne exigua Göeldi, 1887 - Pereira, Lair Victor; Ferraz, Silamar; Maffia de Oliveira, Laede (Revista Ceres, 2025)
The effects of some carbamate nematicides and organic phosphorus insecticides on Meloidogyne erigua were investigated under greenhouse conditions. Their lateral translocation in the roots of coffee seedlings was also evaluated using the «split-root» technique. The products and their dosages in mg a.i./kg of soil were: Aldicarb, 10 and 20; Carbofuran, 50 and 100; Oxamyl, 60 and 120; Dissulfoton, 25; and, Phorate, 50. All the products showed a direct effect by counting the number of galls, when compared with the checks, at the 5% level (Tukey’s test). Oxamyl and Aldicarb were more effective than Phorate. Oxamyl was the only material to show lateral translocation.